Science Journalism in Postcolonial India: Mapping the Political Economy of Ayurveda in Digital News - Dowling, David O.; Subin, Paul (Taylor and Francis Group, 2026)
As the alternative medicine system that has emerged in recent years as India’s top-earning export through its pharmaceuticals, oils, and herbs, Ayurveda has become central to science journalism since the 2020 outbreak of COVID-19. Its status as a symbol of the Indian nation is now contested across digital news outlets, pitting polarized proponents led by Prime Minister Narendra Modi against advocates of modern Western medicine. Science journalism thus plays a key role in India’s pursuit of universal healthcare and economic growth, twin goals the government claims Ayurveda can jointly achieve. Using Nguyen’s decolonized and dewesternized normative framework for assessing science journalism in the Global South, this study maps the political economy of Ayurveda in postcolonial India’s digital news media, offering critical analysis from the daily press to nonprofit magazines. Coverage ranges from defenses of Ayurveda’s traditional epistemic authority to investigations exposing surgical risks and pharmaceutical toxicity, alongside a third strand encouraging dialogue between knowledge systems. Findings indicate that despite vocal dissent from segments of India’s scientific community and limited advocacy for collaborative approaches, news coverage largely reflects Modi’s support for Ayurvedic institutions and industry.
Keywords: 63 Sociología::6306 Sociología del trabajo::6306.07 Sociología de los medios de comunicación de masas; ODS 3 - Salud y bienestar; ODS 10 - Reducción de las desigualdades; science journalism; India; Ayurveda; political economy; medical reporting; Global South